English learning in support of environmental action: promoting environmental and scientific literacies through the application of a didactic sequence - Sanches, Bruno Silva (2023)
Presently, human society and the natural environment confront one of the most significant challenges of the century—the anthropogenic climate crisis. This crisis poses imminent threats to the survival of Earth's biodiversity (Cahil et al, 2013). Notwithstanding, the approaches to environmental education within educational institutions often appear to leave the efficacy of subsequent action to chance (Cristovão, Sanches & Smart, 2022; Gola, 2017; Srbinovsky, 2013; Stibbe, 2004), particularly regarding the pivotal role that language instruction should assume in furnishing the essential affordances necessary to translate accumulated knowledge into tangible action. To address these challenges comprehensively, the present study embarked on an investigation into the role of language learning, specifically English in our context, and the promotion of environmental and scientific through the application of a didactic sequence (DS). The backdrop of our intervention encompassed a public-school institute located in Londrina, Paraná, southern Brazil. Due to the constraints imposed by COVID-19 lockdown measures, lessons were taught through online platforms. The modules of the DS centred on language acquisition, explorations of environmental concerns both local to Londrina and globally, and strategies to address them through the medium of English. The underlying nature of this study is qualitative and grounded in action research. Our first objective was to explore and deliberate upon the potential affordances that a DS could offer for the concurrent advancement of language skills and literacies. The subsequent objective aimed to discern indicators of growth through the textual outputs of the students during asynchronous lessons. Lastly, our intention was interpreting and articulating the ontological viewpoints students held concerning the environment as evidenced in their final productions. In pursuit of the first objective, a meticulously constructed didactic sequence was devised to facilitate data collection. The second objective necessitated the formulation of reflective questionnaires, thoughtfully administered during asynchronous lessons. The data pertinent to the third objective was extracted through meticulous analysis of the students' final productions. The outcomes highlight substantial levels of affordances facilitated by the DS, reflecting discernible shifts towards enhanced literacy and linguistic proficiency during asynchronous lessons. Regarding our last objective, our findings suggest the adoption of a biocentric perspective in the students' final productions. The findings also suggest discernible developmental episodes, yet prolonged time and collaboration with additional social institutions are needed to solidify these advancements in the long term. Regarding language acquisition, we believe that although limited, the affordances created made possible the wider understanding of the relance of English as an ally in promoting environmental protection to a wider audience. We anticipate that our endeavours will contribute to the evolution of novel pedagogical approaches in language teaching, fostering substantive societal transformations and nurturing an enduring commitment to Earth's preservation and protection.